The Impact of Cracked Soil and Weathering on Slope Stability Against Landslides in Hilly Regions with Heavy Rainfall - Putu tantri Kumala sari; Mila K. Wardani (Department of Civil Engineering, Politeknik Negeri Bandung, 2024)
Landslides are frequent events occurring in hilly regions of Pacitan-Indonesia, specifically beneath High Voltage Air Line (SUTT) tower. These events occur during the rainy season, with a monthly and daily intensity of 1,000 mm and 300 mm, respectively. Therefore, this study aims to identify the causes of landslides in hilly regions with good soil conditions influenced by weathering and cracks. The field observations of geotechnical and geophysical were carried out including Electrical Resistivity Tomography (ERT) and Induced Polarization (IP). The results of geotechnical testing showed that soil conditions were generally stiff, while ERT and IP tests indicated a layer with weathering and cracks. Numerical modeling was also performed using limit equilibrium and finite element methods to simulate the impact of soil weathering and cracks. The results showed that the presence of cracks and weathering in soil at landslide location could significantly reduce slope stability, particularly during heavy rainfall. Additionally, the number of cracks and seepage parameter values in weathered soil influenced slope stability, potentially leading to landslides.